The ’Beograd na vodi’ masterplan. Belgrade’s latest identity make over - van der Hoeven, Frank; Ivković, Milena (project baikal, 2014)
Foreign investment by the United Arab Emirates in the ’Beograd na vodi’ master plan sets the stage for the largest urban development in the Serbian capital since the planning of Novi Beograd. While the government embraces the plan as an instrument to spur economic growth in Serbia, critics are more cautious and warn for cliche corporate development.